Analisis Implementasi Sistem Primary-Care BPJS di Puskesmas Wilayah Kota Kabupaten Sumedang - Eri Yulianti; Diana Barsasella (STIKes Persada Husada Indonesia, 2015)
On 1st January 2014 primary-care BPJS began to be applied to support the implementation of BPJS services at Community Health Centers. This system is implemented by all community health centers in Indonesia, inclusive of the 32 community health centers in the Sumedang District. Based on the observation results at the community health centers in the city area in the implementation of the of the primary-care system, there were several problems among others, lack of facilities liked computers, printers and internet network, also frequent system errors. The purpose of this study is to find out primary-care system implementation overviews at Sumedang City District community health centers. Method used in the study was qualitative with phenomenology approach and used HIPO analysis model. There were 3 informant groups in this study, i.e. informant group of 6 primary-care users, key informant group of 5 community health center Heads and 1 Head of administration, and support informant group being the Primary Services Head Management of Sumedang District BPJS. Data collection process comprised of in-depth interviews and observations. Study results showed that input factors made up of knowledge was good, good users’ skill, very minimized communication, inadequate resources comprised of human, facilities, budget and minimal information, acceptable users’ attitude and inadequate bureaucratic structure due to unavailability of SOP. Process comprised of data collection still inaccurate, process undone, data presentation accommodated to Community Health Centers needs and data analysis accommodating number of visitations. Output in the system implementation in the form of community health centers visitation reports for BPJS still need to be expanded for the sake of supporting primary-care system implementation optimization at community health centers.